Debata parlamentarna poświęcona rozgraniczaniu nieruchomości jako płaszczyzna wymiany idei politycznych i prawnych w Królestwie Polskim - Kania, Rafał (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2017)
Contemporary research concept of the history of the political and legal thought includes various sources of information about opinions on politics, state and law that appeared in the past. One of them comprises the debate of the parliament. The article concentrates on the discussion about the boundary line of land property that took place in the Polish Parliament (Sejm) in 1818. The bill of act divided Members of Parliament into two different groups. The first party, dominant, supported the project of the new law that was prepared by the government (Rada Stanu). They thought that it is important to give legal certainty to owners of land property. The second group was formed by Members of Parliament who opposed voting in favour of the project, which in their opinion extremely invaded human privacy and freedom. The content of the debate also presents major conceptions of the system of government and the social order that prevailed in the Kingdom of Poland.